2020
DOI: 10.1037/dev0001098
|View full text |Cite
|
Sign up to set email alerts
|

Three-year-olds’ spatial language comprehension and links with mathematics and spatial performance.

Abstract: Early spatial skills predict the development of later spatial and mathematical skills. Yet, it is unclear how comprehension of the words that capture spatial relations, words like behind and under, might be associated with children’s early spatial and mathematics skills. The current study addressed this question by conducting a moderated mediation model to test the potential moderating effects of group factors, such as socioeconomic status (SES) and gender, on the possible mediation of spatial language compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 73 publications
(119 reference statements)
1
38
0
Order By: Relevance
“…Spatial language is the language of spatial concepts and relationships, usually consisting of words and phrases used to describe the spatial relationship between objects and attributes (Bower et al 2020). Different languages have their linguistic systems to encode spatial information to express spatial concepts and spatial relationships (Bower et al 2020;Bowerman and Choi 2003).…”
Section: Spatial Language and Its Semantic Categoriesmentioning
confidence: 99%
See 3 more Smart Citations
“…Spatial language is the language of spatial concepts and relationships, usually consisting of words and phrases used to describe the spatial relationship between objects and attributes (Bower et al 2020). Different languages have their linguistic systems to encode spatial information to express spatial concepts and spatial relationships (Bower et al 2020;Bowerman and Choi 2003).…”
Section: Spatial Language and Its Semantic Categoriesmentioning
confidence: 99%
“…Spatial language is the language of spatial concepts and relationships, usually consisting of words and phrases used to describe the spatial relationship between objects and attributes (Bower et al 2020). Different languages have their linguistic systems to encode spatial information to express spatial concepts and spatial relationships (Bower et al 2020;Bowerman and Choi 2003). Bowerman (1996) proposed the 'spatial semantic categories' that could be used in human cognition to distinguish the motion or location of objects in space, thereby meeting the need for communications.…”
Section: Spatial Language and Its Semantic Categoriesmentioning
confidence: 99%
See 2 more Smart Citations
“…There is growing evidence that children from lower-income families lag behind their peers from mid-and high-socioeconomic status (SES) families in terms of mathematical knowledge and that there is wide variability in the amount of caregiver-child math talk in their informal learning environments (Starkey et al, 2004;Ramani et al, 2015;Son and Hur, 2020). Similar differences are also found in the domain of color and shape talk, where lower-income families use significantly fewer spatial words during conversations compared to their higher-income peers (Bower et al, 2020;Verdine et al, 2014b). However, several studies have demonstrated that brief interventions can improve conversations between caregivers and children from lower-income families, particularly within informal learning environments such as grocery stores, libraries, bus stops, or at home (Starkey and Klein, 2000;Siegler and Ramani, 2008;Ridge et al, 2015;Hassinger-Das et al, 2020b).…”
Section: Introductionmentioning
confidence: 98%